Surface reconstruction of Ni doped Co–Fe Prussian blue analogues for enhanced oxygen evolution. Issue 3 (18th December 2020) - Hou, Jingting; Tang, Zeming; Wei, Keyan; Lai, Qingxue; Liang, Yanyu
Abstract : The in situ generated Ni(Co) oxyhydroxides sites transform the RDS for OER, thus achieving significantly accelerated catalysis kinetics. Abstract : An efficient oxygen evolution reaction (OER) process requires fast kinetics to increase water splitting efficiency. Prussian blue analogues (PBAs) as a promising OER electrocatalyst have attracted more attention due to their surface reconstruction to form active oxyhydroxides layer during the continuous OER process. However, the research on how to optimize the surface reconstruction of PBAs is still lacking. Herein, Ni-doped Co–Fe PBAs nanocubes were designed as an efficient OER catalyst to promote surface-selective etch and reconstruction into metal oxyhydroxides during the activation process. Structural characterization and analysis indicated that the incorporation of Ni enhanced the surface reconstruction, and the resulted metal oxyhydroxides acted as the major active sites for OER electrocatalysis. The rate-determining step is converted to the final O2 release step after the activation process, which significantly accelerates OER kinetics. As a result, the NiCo–Fe PBAs electrode exhibits excellent catalytic activity with a low overpotential of 274 mV under a current density of 100 mA cm −2 and Tafel slope of 36 mV dec −1 .